E-Prescribing: Benefit, Barrier, and Adopting Challenge in Electronic Prescribing - Oktarlina, Rasmi Zakiah (Journal of Medicine, 2020)
E-Prescribing system provides prescribing drugs electronically that can be a stand-alone system or be integrated with Electronic Health Records (EHRs) system. When implementing an E-Prescribing system, we need to consider it’s benefits and barriers, also adopting factors that can affect the success of the implementation. The main advantage of using an E-Prescribing system is to increase patient safety, meanwhile, the biggest barriers and challenges are it’s cost-related and adaptation by health facilities and related health workers. This article review provides information about E-prescribing and it’s elements to help for a better understanding of the system and to give some insights before adopting the e-prescribing system. J MEDICINE JUL 2020; 21 (2) : 98-101